-73-8x=10x+17

Simple and best practice solution for -73-8x=10x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -73-8x=10x+17 equation:


Simplifying
-73 + -8x = 10x + 17

Reorder the terms:
-73 + -8x = 17 + 10x

Solving
-73 + -8x = 17 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-73 + -8x + -10x = 17 + 10x + -10x

Combine like terms: -8x + -10x = -18x
-73 + -18x = 17 + 10x + -10x

Combine like terms: 10x + -10x = 0
-73 + -18x = 17 + 0
-73 + -18x = 17

Add '73' to each side of the equation.
-73 + 73 + -18x = 17 + 73

Combine like terms: -73 + 73 = 0
0 + -18x = 17 + 73
-18x = 17 + 73

Combine like terms: 17 + 73 = 90
-18x = 90

Divide each side by '-18'.
x = -5

Simplifying
x = -5

See similar equations:

| 199-6x=39x+24 | | 2x+13=-11-10x | | 12-9x=43-16x | | 129-3x=5x+17 | | -132-8x=9x+21 | | 10n=90 | | 4x+14=-28-10x | | -51-3x=9-9x | | 141-6x=2x+21 | | (4d-2)-(d-2)=3d | | 23(13x-5)=23 | | 69-3x=9-9x | | 4x+6=54-2x | | x^2+14x+45=0 | | -1-6x=6-7x | | 6x+v=2x+w | | -6b=10 | | 2+6x=42+x | | 4x-4=14x-124 | | 4x^2-20x-9=0 | | 4x^2-8x-3=0 | | 3x+30=5x+12 | | 2x^2+10x=3 | | 4(a+2b-6)+5(2a+6b-8)= | | 5=3n-6 | | 5x^2-35x+25=0 | | 8+4(x-1)-5(x-3)=2(5-2x) | | 3x^2+15x-36=0 | | 12x+9=10x+15 | | .6666666667(18x-12)=7-3(-4x-3) | | 83-3x=42x+18 | | -5+6d+3=34 |

Equations solver categories